Inhibitory Effects of Novel SphK2 Inhibitors on Migration of Cancer Cells - Lee, Euiyeon; Jung, Junghyun; Jung, Deokho; Mok, Chang S.; Jeon, Hyunjin; Park, Chang-Seo; Jang, Wonhee; Kwon, Youngeun (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Cell migration is an essential process for survival and differentiation of mammalian cells. Numerous diseases are induced or influenced by inappropriate regulation of cell migration, which plays a key role in cancer cell metastasis. In fact, very few anti-metastasis drugs are available on the market. SphKs are enzymes that convert sphingosine to sphingosine-1-phosphate (S1P) and are known to control various cellular functions, including migration of cells. In human, SphK2 is known to promote apoptosis, suppresses cell growth, and controls cell migration; in addition, the specific ablation of SphK2 activity was reported to inhibit cancer cell metastasis. Objective: The previously identified SG12 and SG14 are synthetic analogs of sphingoid and can specifically inhibit the functions of SphK2. We investigated the effects of the SphK2 specific inhibitors on the migratory behavior of cells. Method: We investigated how SG12 and SG14 affect cell migration by monitoring both cumulative and individual cell migration behavior using HeLa cells. Results: SG12 and SG14 mutually showed stronger inhibitory effects with less cytotoxicity compared with a general SphK inhibitor, N,N-dimethylsphingosine (DMS). The mechanistic aspects of specific SphK2 inhibition were studied by examining actin filamentation and the expression levels of motility-related genes. Conclusion: The data revealed that SG12 and SG14 resemble DMS in decreasing overall cell motility, but differ in that they differentially affect motility parameters and motility-related signal transduction pathways and therefore actin polymerization, which are not altered by DMS. Our findings show that SphK2 inhibitors are putative candidates for anti-metastatic drugs.
Keywords: motility parameters